PENERAPAN MODUL LATIH PORTABLE ANALOG/DIGITAL SEBAGAI MEDIA PEMBELAJARAN SISTEM MIKROKONTROLER - Sukmawan, Aning (2013)
This research about the implementation of analog or digital portable training modul as a learning media in microcontroller system , purpose of this research is for developing a learning media which can increase the result of study of the student in microcontroller system competence standart. Purpose of this research also to know the effectivity of digital portable training modul based on the result of study of the student in microcontroller system competence standart. Research model that was used is research and development approach with descriptive and evaluative approach with the stage until limited test. The assessment of learning process can be seen from increasing cognitive, affective, and psychomotoric aspect. The sample that was used in this research consist of 30 students of Teknik Mekatronika in SMKN 2 Cimahi. The collecting data was done by giving the questionnaire, observation, pretest and post test. The result of this research showed that the implementation of analog/digital portable module based on teachers and students opinion, it obtained a response that shows the result with classification in a good stage, it means that this training module is effective to used as learning media of microcontroller system. Based on testing the hypothesis with using left-side proportion test in cognitive, affective, and psychomotoric domain, it will obtain the Zcalculation score is bigger than Ztable. This result shows that the implementation of analog/digital portable training module as learning media in microcontroller system is effective toward the increasing of learning result of students cognitively, affectively, and psychomotorically. Key words : Learning media, analog or digital portable training modul, Research and Development, Microcontroller system. Penelitian mengenai penerapan modul latih portable analog/digital sebagai media pembelajaran dalam sistem mikrokontroler , penelitian ini bertujuan untuk pengembangan suatu media pembelajaran yang dapat meningkatkan hasil belajar siswa pada standar kompetensi sistem mikrokontroler. Penelitian ini juga bertujuan untuk mengetahui efektifitas penerapan modul latih portable analog/digital ditinjau dari hasil belajar siswa pada standar kompetensi sistem mikrokontroler. Model penelitian yang digunakan merupakan pendekatan penelitian dan pengembangan (research and development) dengan pendekatan deskriptif dan evaluatif dengan tahapan sampai uji coba terbatas saja. Penilaian proses hasil belajar dilihat dari peningkatan aspek kognitif, afektif, dan psikomotorik. Sampel yang digunakan pada penelitian terdiri dari 30 orang siswa program keahlian Teknik Mekatronika di SMK Negeri 2 Cimahi. Pengumpulan data dilakukan dengan pemberian angket, observasi dan tes pretest dan posttest. Hasil penelitian menunjukan bahwa penerapan modul latih portable analog/digital berdasarkan pendapat guru dan siswa mendapatkan respon yang menunjukkan hasil dengan klasifikasi pada tingkat yang baik, yang artinya modul latih ini efektif digunakan sebagai media pembelajaran sistem mikrokontroler. Berdasarkan uji hipotesis dengan menggunakan uji proporsi pihak kiri pada ranah kognitif, afektif, dan Psikomotor, diperoleh nilai Zhitung lebih besar dari Ztabel. Hal ini menunjukkan bahwa penerapan modul latih portable analog/digital sebagai media pembelajaran sistem mikrokontoler efektif terhadap peningkatan hasil belajar kognitif, afektif, dan psikomotor siswa. Kata Kunci : Media Pembelajaran, Modul Latih Portable Analog/Digital, Research and Development, Sistem Mikrokontroler.